2018
DOI: 10.1186/s13561-018-0206-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of Child Maltreatment with South African Adults’ Wages: Evidence from the Cape Area Panel Study

Abstract: Child maltreatment is a prevalent public health problem in both developed and developing countries. While many studies have investigated the relationship between violence against children and health of the victims, little is known about the long term economic consequences of child maltreatment, especially in developing countries. Using data from the Cape Area Panel Study, this paper applies Heckman selection models to investigate the relationship between childhood maltreatment and young adults’ wages in South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The justification for the use of this variable is that it might affect the likelihood of employment participation, but an individual's earning level is unlikely to depend on family size. In addition, different studies used the number or presence of children, which is highly correlated with family size, in the selection equation to satisfy the exclusion restriction [ [70] , [71] , [72] ]. Considering the lack of tests for the validity of the instrument used and possible concerns about the justification, the study is limited to describing associations without making causal inferences.…”
Section: Resultsmentioning
confidence: 99%
“…The justification for the use of this variable is that it might affect the likelihood of employment participation, but an individual's earning level is unlikely to depend on family size. In addition, different studies used the number or presence of children, which is highly correlated with family size, in the selection equation to satisfy the exclusion restriction [ [70] , [71] , [72] ]. Considering the lack of tests for the validity of the instrument used and possible concerns about the justification, the study is limited to describing associations without making causal inferences.…”
Section: Resultsmentioning
confidence: 99%
“…A study using cross-sectional data from the Egypt Demographic and Health Survey among children aged 5–17 years found that experiencing violence (physical and severe punishment) was associated with hazardous labour [ 47 ]. Longitudinal studies in South Africa, the US, the UK, Denmark, and Norway find that child maltreatment increases the risk of adverse work outcomes [ 29 , 30 , 48 , 49 , 50 ]. A systematic review of longitudinal research on child maltreatment and later work outcomes (reduced income, unemployment, lower level of job skill, and fewer assets) further underscores that that childhood experiences of maltreatment increased the risk of adverse work outcomes after accounting for family of origin socio-economic status [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies in the USA [ 28 ] and Norway [ 29 ] found that children who experienced violence had lower levels of employment and earnings in adulthood compared to those who did not experience violence. Of the limited research in low- and middle-income countries (LMICs), a longitudinal study in Cape Town found that any experience of physical or emotional abuse during childhood was associated with a later 12% loss of wages, with larger wage losses among young women compared to men [ 30 ]. There is also evidence to suggest that childhood violence leads to poorer educational outcomes [ 31 ], which affects both access to work and wages [ 32 ].…”
Section: Introductionmentioning
confidence: 99%